1974
DOI: 10.1007/bf00577830
|View full text |Cite
|
Sign up to set email alerts
|

Developmental capacities of benign and malignant neoplasms ofDrosophila

Abstract: The developmental properties of three neoplasms found in lethal mutants ofDrosophila melanogaster were studied and compared with the development of the corresponding wild-type organs. Two of these neoplasms are found in the late larval lethal mutant,lethal (2) giant larvae (l(2)gl) and its allele,lethal (2) giant larvae (l(2)gl). The third neoplasm occurs in the hemizygous lethal male embryos of the mutantNotch (Df(1)N).The mutantsl(2)gl andl(2)gl were shown to possess defects involving imaginal primordia of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(97 citation statements)
references
References 71 publications
1
95
0
Order By: Relevance
“…Loss of PAR3 will result in inappropriate activity along these pathways, with sometimes deleterious consequences (15). The potential of polarity proteins as tumor suppressors has been recognized since early studies in Drosophila development found that they restrain tissue proliferation (41). Loss of polarity genes in Drosophila can also synergize with oncogenes to generate tumors that invade and metastasize aggressively (10,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of PAR3 will result in inappropriate activity along these pathways, with sometimes deleterious consequences (15). The potential of polarity proteins as tumor suppressors has been recognized since early studies in Drosophila development found that they restrain tissue proliferation (41). Loss of polarity genes in Drosophila can also synergize with oncogenes to generate tumors that invade and metastasize aggressively (10,42,43).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in neuroblastomas from dlg or lgl mutants, at least a proportion of the tumour cells acquire an unlimited capacity for self-renewal (reviewed by Gonzalez, 2007). These brain tumours can be continually propagated through successive transplants in adult host flies, raising the possibility that tumour growth is driven by the deregulation of stem cell self-renewal pathways (Gateff and Schneiderman, 1974;Woodhouse et al, 1998;Caussinus and Gonzalez, 2005). Although it is not known if epithelial tumours develop from stem-like cells (in fact, imaginal discs are not known to contain stem cells, even though they are capable of unlimited selfrenewal), work in Drosophila has long implicated a stem cell origin for neuroblastomas (reviewed by Januschke and Gonzalez, 2008).…”
Section: Control Of Self-renewal and Differentiationmentioning
confidence: 99%
“…The Scribble/Dlg/Lgl polarity module Scribble, Dlg and Lgl were originally identified in the genetically tractable model organism Drosophila, in which homozygous mutants in any of the genes results in the loss of apicobasal cell polarity and neoplastic tissue overgrowth (Gateff and Schneiderman, 1974;Mechler et al, 1985;Woods and Bryant, 1989;. Due to the similarity in their mutant phenotypes and the genetic interactions observed between them, it has been surmised that Scribble, Dlg and Lgl function in a common pathway to regulate the establishment and maintenance of apicobasal polarity in epithelial cells .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 The p127 protein forms large homomeric complexes 6,7 and is associated with a series of proteins, among which were identified the heavy chain of nonmuscle myosin-II, 6 designated thereafter as myosin-II, and a yet unknown serine-kinase. 8 Activation of this kinase leads to specific phosphorylation of p127 and results in the dissociation of myosin-II from p127 without affecting its homomerisation.…”
Section: Introductionmentioning
confidence: 99%